Phasage des travaux et organisations transitoires : quels rôles pour l’ergonome ? - François Daniellou; Jacques Escouteloup; Joffrey Beaujouan (Activités)
Extensions to occupied premises are one of the major categories of architectural situation, raising the issue of coordinating construction work with the continuous operation of the establishment. The works schedule is often determined by the architects on the basis of technical and administrative constraints. In many cases, temporary organisation methods to ensure smooth operation during building are not planned in advance. Ergonomics has often focused on understanding the shift from Situation A to Situation B in an architectural context but has devoted less attention to the intermediate stages between A and B and their impact on occupants’ health and the efficiency of the establishment. This paper examines various examples of this type of project and suggests how ergonomists may help to reconcile continued operation and building work by: (1) encouraging the two professional groups to meet and discuss the issues, (2) using simulations to determine the broad outlines of the schedule, (3) helping occupants to define temporary organisation methods and (4) adjusting those forms of organisation to major stages in the schedule.